The correlation between diabetes mellitus and depression - Madera, Magdalena; Mazur, Sylwia; Mazur, Agata; Bizan, Aleksy; Nagórska, Emilia; Marcinkowski, Krzysztof; Strus, Karolina; Kublińska, Aleksandra; Zdunek, Roksana; Dąbrowska, Natalia (Journal of Education, Health and Sport, 2024)
Depression is the most prevalent mental health condition. It’s estimated that nearly 5% of adults suffer from this disorder globally. Depression is marked by ongoing sadness and a loss of interest or pleasure in activities that were once enjoyable or fulfilling. It can also lead to disruptions in sleep and eating patterns. Common symptoms include fatigue and difficulty concentrating. According to WHO diabetes is a chronic, metabolic disease characterized by elevated levels of blood glucose which leads to the damage of the heart, blood vessels, eyes, kidneys and nerves. Nowadays the occurrence of diabetes mellitus, obesity and depression is getting higher and higher. Both conditions stand as prominent health issues in today’s society. Recent pandemic, wars, problems of the current world can cause depression and anxiety disorders. The fast-paced nature of our lives, work-life balance issues, sedentary habits, and time constraints can lead to opting for fast food and neglecting a healthy diet. People with diabetes are more prone to experiencing depression. Moreover, a significant portion of cases remains underdiagnosed.